Produção imobiliária e novas dinâmicas de expansão urbana em Patos e Cajazeiras (PB) - Araújo, Luciana Medeiros de (2017)
This doctoral thesis aims to analyze the recent real estate construction practice and the new dynamics of urban sprawl between 2009 and 2015, in the cities of Patos and Cajazeiras, both located in Paraíba, Northeast Brazil. Such a time frame is based on the implementation of the government program Minha Casa Minha Vida, which reaffirmed the crucial place of the State as a propellant of real estate development, aimed to housing of social interest, as well as the market. The State's interposition in the real estate sector, through this program, redefined the subsidies guidelines of low-income housing credit. In addition, it assured real estate loans to construction companies for the private promotion of market housing, covering segments of the population of medium and high income. Thus, the measures taken by the State provided a boost to the urban economy, mobility of capital and, consequently, convergence of local and non-local private real estate agents, particularly developers and builders, with the capability to invest, intervene and transform the real estate sector and the urban space of the analyzed cities. The objective of the research was to demonstrate the mobility of capital and the formation of partnerships between the producer agents of urban space, including the State, with a view to real estate development, by means of land parceling of periurban rural properties for the implementation of housing estates. In Patos and Cajazeiras, new dynamics of territorial expansion emerged under the capitalist logic of urban production, and redefined the supplies and appreciation of urbanized commercial estates and new housing units, thus increasing real estate speculation. The celerity of this parceling turned the rural land into urban land, and produced a large number of estates and housing prepared to reproduce the circuit and accumulation of capital and the increase of urban incomes for real estate developers. Socio-spatial contradictions and conflicts of interest between the different real estate agents emerged from this. It sustains that the interposition of the State, with emphasis on that coming from the Federal level, and the convergence of real estate agents for those cities, produced new dynamics of rising urban expansion. Such growth accommodated the cities as niches of reproduction and accumulation of different commercial capital fractions, whose investments were made in the real estate sector. It should be noted that this is a reproducible process in other cities. The theoretical framework of this research was based on references related to the capitalist production of the urban space and on primary data from the land registries of real estates of the cities investigated. Likewise, secondary data were used, as well as surveys directed to municipalities’ administration, CREA / PB, TCE / PB, CEHAP / PB, IBGE, CEF, Ministry of Cities, Ministry of Labor, among other institutions. Regarding the field work, we conducted semi-structured interviews, informal talks, photographs and annotations about the surrounding infrastructure. To demonstrate the spatialization of real estate production and urban expansion, thematic cartograms and images taken from Google Earth were used.